The Conflict of Pro-Islamist and Nationalist Militia Groups in Libya And Its Impact On Economic Growth For The 2011-2019 Period - hannase, Mul; Amril, Ali (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
This study aims to analyze the competition between pro-Islamist and nationalist militia groups in the control of economic resources and it influences on Libya’s economic growth. The approach used is a qualitative approach. Conflict theory, greed and grievance theory, and economic growth theories are used to analyze Libya's post-revolution political economy. This research shows that the competition between militia groups over economic resources has occurred since the transition period of the Libyan government in 2011 and continues until this writing. Economic resources contested include oil, trade centers, banks, trade routes in country borders, airports, and important positions in government. Conflicting militia groups often use violence to obtain economic and political benefits. This is what creates the complexity of the Libyan political conflict. This research concludes that the political conflicts that are preoccupied with the competition of various internal and external actors to fight over economic resources and power, have a negative influence on economic growth and social life of the Libyan people.